Nano-scale mechanical behaviors and material removal mechanisms of zirconia ceramics sintered at various temperatures. Issue 23 (1st December 2021) - Ji, Min; Xu, Jinyang; Li, Linfeng; Yu, Dedong; Chen, Ming; El Mansori, Mohamed
Abstract: The present work aims to address the effects of the sintering temperature (800–1500 °C) on the mechanical properties and material removal mechanisms of 3 mol% yttria-stabilized tetragonal zirconia polycrystals (3Y-TZP) based on a series of nanoindentation and nanoscratch experiments. The impacts of the sintering temperature on the mechanical properties, including plasticity, deformation behavior, indentation energies, and cracking resistance were rigorously studied. The acquired results indicate that 1100 °C signifies the transition threshold for the ceramic microstructure, leading to the entirely different mechanical properties and indentation responses for materials sintered at temperatures lower or higher than the threshold value. Moreover, 1100 °C is also a transition threshold of the material removal mechanism, before which the material removal mechanism is dominated by the plastic regime, and beyond which, the material removal mechanism tends to show ductile-brittle characteristics.